Algeria : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2012)
This paper analyzes Algeria's unemployment and labor market developments and assesses the factors that may hamper employment creation. It estimates employment-to-GDP elasticity for Algeria's main sectors and different age groups, and assesses the effect of improvements in Algeria's labor market flexibility on unemployment outcomes. The results on the relation between labor market institutions and unemployment show that improvement in labor market conditions in Algeria could have a significant effect in reducing unemployment both in the short and medium term.